Analysis on Sealing Performance for a New Type of Rubber Saddle-shaped Sealing Ring Based on AQAQUS. (2015) - Zhou, S.M.; Chen, P.; Shi, Y.
Abstract: At present, rubber sealing C-ring has been widely used in the quick opening end closures for natural gas transmission filters. In this paper, a new saddle-shaped sealing ring was proposed for substituting of traditional C-ring. It has the feature of floatability that makes the assembling and disassembling easier than before. In addition, its sealing and load-bearing performance is superior than C-ring based on the analysis by using FEM software ABAQUS. At the same time, the reasonable range and values for the key parameters that affecting the sealing performance of saddle-shaped sealing ring were discussed and recommended.